Bridging Gaps in Online Arabic Language Instruction : Addressing Key Challenges in Higher Education Institutions - Nur Jannah, Jamil; Roswati, Abdul Rashid; Farah Hussan, Sahib; Mazlina, Ahmad; Kasyfullah, Abd kadir; Suria Hani, Ibrahim; Che Mohd Zaid, Yusof; Roslina, Mamat; Rokiah, Paee; Min Sung, Cho (Universiti Sultan Azlan Shah, Perak, 2024)
The rapid shift to online education, accelerated by the global pandemic, has highlighted significant challenges in Arabic language instruction, particularly in Malaysia's public higher education sector. This study investigates the key challenges, strategies, and skills required for effective online foreign language instruction in higher education institutions in Malaysia. Four main themes emerged through interviews with five Arabic language instructors: online teaching and learning facilities, delivery platforms, student attitudes and behaviours, and learning outcomes. Significant challenges include unreliable internet connectivity, student disengagement, and difficulty assessing language proficiency. Instructors have responded by adopting strategies such asrecorded lectures, interactive activities, and tailored instruction, aligning with modern pedagogical practices. The findings underscore the need for comprehensive online Arabic language education skills, including pedagogical, managerial, and content-specific skills. This complexity is further highlighted by the practical implications of the study, which include a focus on student-centred approaches, technological investment, and continuous professional development. While the study's reliance on self-reported data limits generalizability, it offers valuable insights into addressing the complex challenges of online Arabic language instruction as a foreign language. Future research should explore the effectiveness of specific interventions and the contextualfactors influencing online Arabic language education.